Antibacterial Evaluation of Plectranthus amboinicus-infused Glass Ionomer Cement Against Streptococcus mutans: An In-vitro Study - Shambavi V Kadam; Vignesh Ravindran (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Dental caries remains one of the most prevalent oral diseases worldwide and is strongly associated with Streptococcus mutans, while conventional Glass Ionomer Cement (GIC) has limited intrinsic antibacterial activity. Therefore, there is a need to develop modified restorative materials with enhanced antimicrobial properties to reduce bacterial colonisation and improve clinical outcomes. Aim: The present preliminary in-vitro study aimed to evaluate and compare the antibacterial efficacy of Plectranthus amboinicus aqueous extract-modified GIC with that of conventional GIC against Streptococcus mutans using Colony-Forming Unit (CFU) enumeration and crystal violet assay. Materials and Methods: This preliminary in-vitro study was conducted in the Department of Microbiology, Saveetha Dental College and Hospitals, Chennai, Tamil Nadu, India, from December 2025 to January 2026. An aqueous extract of Plectranthus amboinicus was prepared and incorporated into Type II GIC (GC Corporation, Tokyo, Japan) to form the test group. At the same time, conventional GIC served as the control group. A total of six cylindrical specimens (5 mm × 2 mm) were fabricated, with three specimens in each group (n=3). Each specimen was incubated with a standardised Streptococcus mutans suspension. Antibacterial activity was evaluated using serial dilution and CFU enumeration. Biofilm biomass was assessed using a crystal violet assay with absorbance measured at 592 nm. All experiments were performed in triplicate for each group. Statistical analysis was carried out using an Independent samples t-test (Welch’s correction), with a p-value